Effects of Online Game and Short Video Behavior on Academic Delay of Gratification - Mediating Effects of Anxiety, Depression and Retrospective Memory - Xia LL; Li JD; Duan F; Zhang J; Mu LL; Wang LJ; Jiao CY; Song X; Wang Z; Chen JX; Wang JJ; Wang Y; et al. (Psychology Research and Behavior Management, 2023)
Ling-Ling Xia,1,* Jun-Da Li,1,* Fan Duan,1,* Jing Zhang,1 Lin-Lin Mu,1 Li-Jin Wang,1 Chen-Yang Jiao,2 Xun Song,1 Ze Wang,1 Jin-Xuan Chen,1 Jing-Jing Wang,1 Yue Wang,1 Xiao-Chu Zhang,1,3 Dong-Liang Jiao1 1School of Mental Health, Bengbu Medical College, Bengbu, People’s Republic of China; 2School of Medical Imaging, Wannan Medical College, Wuhu, People’s Republic of China; 3CAS Key Laboratory of Brain Function and Disease and School of Life Sciences, University of Science and Technology of China, Hefei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dong-Liang Jiao; Xiao-Chu Zhang, Email jdl3925697@163.com; zxcustc@ustc.edu.cnObjective: Learner dependence on short videos has many pitfalls for learning outcomes, but the negative effects of excessive short video use have been little discussed in the learning psychology literature. Therefore, this study investigated the effects of excessive short video use on anxiety, depression, prospective memory, and academically delayed gratification (ADOG) in relation to online gaming-related behaviours, and explored the possible mechanisms by which excessive online gaming and short video use may lead to decreased ADOG, to expand our understanding of excessive short video use.Methods: Based on the whole class random sampling method, a questionnaire survey was conducted among college students in Northern Anhui, China from May 7 to July 27, 2022. The questionnaires included the Generalized Anxiety Disorder Scale (GAD-7), Patient Health Questionnaire Scale (PHQ-9), Prospective and Retrospective Memory (PRM) Questionnaire, and ADOG Scale.Results: A total of 1016 participants completed the survey. The study found that of all the internet behaviors, 20.8% of the college students mainly played online games, 43.9% mainly played short videos, and 35.3% conducted other online behaviors. When compared with other internet behaviors, online gaming and short video behaviors can cause more serious anxiety/depression and worse PRM and ADOG scores. As time spent playing online games and short videos increased, anxiety and depression became worse, and the scores for PRM and ADOG also declined. Anxiety, depression, and PRM mediate the relationship between time spent on online gaming/short videos and ADOG.Conclusion: Excessive short videos behaviour may produce the same psychological problems and learning problems as online gaming disorder. Excessive short video and online gaming behaviors may affect ADOG performance through anxiety, depression, and prospective memory. These findings could be used as a basis for future studies on the improvement of ADOG.Keywords: short video, online games, anxiety, depression, prospective memory, academic delay of gratification